Hantaviruses induce cell type- and viral species-specific host microRNA expression signatures - Shin, Ok Sarah (2013)
The mechanisms of hantavirus-induced modulation of host cellular immunity remain poorly understood. Recently, microRNAs (miRNAs) have emerged as a class of essential regulators of host immune response genes. To ascertain if differential host miRNA expression toward representative hantavirus species correlated with immune response genes, miRNA expression profiles were analyzed in human endothelial cells, macrophages and epithelial cells infected with pathogenic and nonpathogenic rodent- and shrew-borne hantaviruses. Distinct miRNA expression profiles were observed in a cell type- and viral species-specific pattern. A subset of miRNAs, including miR-151-5p and miR-1973, were differentially expressed between Hantaan virus and Prospect Hill virus. Pathway analyses confirmed that the targets of selected miRNAs were associated with inflammatory responses and innate immune receptor-mediated signaling pathways. Our data suggest that differential immune responses following hantavirus infection may be regulated in part by cellular miRNA through dysregulation of genes critical to the inflammatory process.